Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD